PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE JIGSAWTERHADAP HASIL BELAJAR IPS TERPADU KELAS VIII - Hevaria Surisno; Yesi Budiarti (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Based on the results of the survey that researcher do, the problem in this study is still a lot of students who have not completed in Learning Outcomes Integrated Social Studies Student Class VIII MTs Muhammadiyah Metro in academic year 2015/2016. The purpose of this research is to know the Influence of Model Jigsaw Cooperative Learning Model Towards Integrated IPS Student Learning of Class VIII Even Semester of MTs Muhammadiyah Metro academic Year 2015/2016. This research is experimental research with population in this research is student class VIII Mts. Muhammadiyah Metro even Semester academic year 2015/2016 which numbered 84 students. Sample of the research is taken by using purposive sampling technique and obtained class VIII.A as experiment class by using model cooperative learning jigsaw type. The result of research data analysis can be seen that tcount> t table or 7.70> 1.71 (table t with dk = 28 and = 0.05) and t arithmetic> t table or 7.70> 2.47 (table t with dk = 28 and α = 0.01), thus Ho is rejected and Ha acceptedor hypothesis accepted. Thus it can be concluded that the use of model Cooperative Learning Type Jigsaw improve the results of learning IPS Integrated students class VIII MTs Muhammadiyah Metro or hypothesis there is a positive influence of using model Cooperative Learning Jigsaw Type of Learning Outcomes Integrated Social Studies Student Class VIII Even Semester MTs Muhammadiyah Metro academic year 2015 / 2016.